2021
DOI: 10.2478/raft-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the 25-Item Connor-Davison Resilience Scale: Preliminary Data for a Romanian Military Population

Abstract: The following study is aimed at investigating the construct validity of the 25-item Connor-Davidson Resilience Scale (CD-RISC 25) on a Romanian military population. The exploratory factor analysis was conducted on 434 male military participants, aged between 24 and 50 years (M = 34.83, S.D. = 6.14) and the confirmatory factor analysis was conducted on a sample of 679 military participants, of 605 men and 74 women, aged between 18 and 59 years (M = 38.37, S.D. = 9.07). Factor analysis of the scale showed it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Findings showed no items had been removed in the current research, and all items have a high factor. The results are broadly consistent with previous studies that showed high internal consistency for the CD-RISC in clinical and general populations [ 22 , 48 50 ] and in contrast to the findings of Giurcă [ 51 ], Velickovic [ 52 ] that some questions and factors were omitted. Our research showed that resilience scores in athletic adolescent girls were higher than in general girl adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Findings showed no items had been removed in the current research, and all items have a high factor. The results are broadly consistent with previous studies that showed high internal consistency for the CD-RISC in clinical and general populations [ 22 , 48 50 ] and in contrast to the findings of Giurcă [ 51 ], Velickovic [ 52 ] that some questions and factors were omitted. Our research showed that resilience scores in athletic adolescent girls were higher than in general girl adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…In countries where a translated CD-RISC had not been developed, such as Latvia, a translated version was created using a forwardbackward translation process. Researchers consistently have reported translations of the CD-RISC are psychometrically valid in Croatia, Greece, Italy, Portugal, and Romania (e.g., Tsigkaropoulou et al, 2018;Anjos et al, 2019;Mikuš et al, 2020;Giurcȃ et al, 2021;Grazzani et al, 2022).…”
Section: Connor-davidson Resilience Scalementioning
confidence: 99%